Hole transport layers in organic solar cells: A review - ALKARSIFI, Riva; ACKERMANN, Jörg; MARGEAT, Olivier (Journal of Metals, Materials and Minerals, 2022)
Thanks to huge research efforts, organic solar cells have become serious candidates in the field of renewable energy sources, with reported power conversion efficiencies above 19% and operating lifetime surpassing decades. In the thin film stack composing the organic solar cell, the transport layers at interfaces play a key role, as important as the photoactive material itself. Both electron (ETL) and hole (HTL) transport layers are indeed directly involved in the efficiency and stability of the devices, due to the very specific properties required for these interfaces. Focusing on the HTL interface, a large number of materials has been used in organic solar cells, such as 2D materials, conductive polymers or transition metal oxides. In this review, we present the evolution and recent advances in HTL materials that have been employed in manufacturing organic solar cells, by describing their properties and deposition processes, and also relating their use with the fullerene or the new non-fullerene acceptors in the active layer.